The Effect of Organizational Citizenship Behavior on Employee Performance - Muhammad Ifan Fadillah; Muhammad Idrus Taba; Andi Reni (Hasanuddin Journal of Business Strategy, 2022)
This study aimed to find out the effects of OCB on Nurses’ performance at Hospital Ibnu Sina Makassar. This is quantitative research with the targeted respondents that are 53 nurses. The data were collected using questionnaires or structured questionnaires, while the data analysis used Partial Least Square PLS. There are 21 indicators evaluated in the OCB, but three indicators were dropped firstly, then followed by four indicators. For the performance, there are 20 indicators evaluated their loading weight parameter that there is only one indicator is dropped due to having loading weight less than 0.5. Of the 18 indicators used to define the construct OCB and 19 indicators for the construct performance, the study found that OCB has a significant positive effect on nurses’ performance